HUBUNGAN LAMA PEMAKAIAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) DENGAN PERUBAHAN AKTIVITAS SEKSUAL PASANGAN USIA SUBUR (PUS) DI PMB TUTIK IDAYANI - Suryani, Ike Yuli; Zakiyyah, Muthmainnah; Wahyuningsih, Sri (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
IUD is a form of reversible long-term contraception and is the most effective method of birth control. The purpose of this study was to determine the correlation between the use of intrauterine devices (IUD) and changes in sexual activity of couples of childbearing age (PUS) at PMB Tutik Idayaani. The research design used in this study is descriptive quantitative with a cross-sectional approach, namely a type of research that emphasizes the time of measurement/observation of independent and dependent variable data only once at a time. the total population in this study was 55 acceptors i and the number of samples was determined using the Slovin formula whichis as many as 44 acceptors with simple random sampling. Technique and statistical tests used chi-square. The results of this study showed that 32 respondents (72.7%) experienced changes in IUD acceptors, while 12 respondents (27.3%) did not experience changes in sexual activity. The results of the chi-square test analysis with a 95% level of confidence obtained p (Sig) was 0.001, the value of p (sig) < α (0.001 < 0.05).There is a correlation between Length of intrauterine contraceptive devices (IUD) Use and changes in sexual activity of partners of childbearing age (PUS) at PMB Tutik Idayani. This research can be used as a reference and information to provide optimal and quality services.